Analisis kesulitan belajar siswa dalam pembelajaran tematik di sekolah dasar - Antika, Novi; Marmoah, Sri; Sularmi, Sularmi (Universitas Sebelas Maret, 2021)
The purpose of this research was to (1) explain the implementation of thematic learning for fifth grade students (2) to describe the learning difficulties of students in implementing thematic learning for fifth grade. This research using descriptive qualitative research methods with a case study approach. Taking research subjects using the Simple Random Sampling Technique by conducting interviews, questionnaires, and document studies on the informants. Data obtained directly from the first source, namely 12 5th grade students, 5th grade teachers, and parents of students. The difficulty in learning the subjects of 5th grade students at SDN Kerten II is caused by factors, namely (1) The results of this research indicate that the implementation of thematic learning at Public Elementary School Kerten 2 Surakarta has not implemented thematic learning properly. Because, students have not been able to integrate between lesson content, in other words, they cannot independently connect one lesson content with another.; and (2) The difficulty of students in implementing thematic learning is also caused by two factors, namely the first internal factors including interest, motivation, and student habits during thematic learning. The low interest of students is related to reading and the habits of students when learning thematic are not disciplined, only doing half of the task, answering briefly and not in accordance with reading sources, and slow in the process. Second, external factors include the conditions of the learning environment of students that are not conducive at home due to disturbances from the surrounding environment where they live close together, the lack of learning room facilities, and the lack of variation in teaching related to the methods and media used.